2018
DOI: 10.33307/entomon.v43i4.404
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic review of the tribe Nymphalini (Lepidoptera: Nymphalidae: Nymphalinae) from western Himalaya, India with special emphasis on external genitalic attributes

Abstract: Taxonomic review for 11 species referable to six genera under the tribe Nymphalini has been presented. Taxonomic characterization, and elucidation of external genitalic attributes, has been done for five species namely, Nymphalis xanthomelas (Esper), Polygonia c-album (Linnaeus), Kaniska canace (Linnaeus), Symbrenthia lilaea (Hewitson) and Symbrenthia hypselis (Godart) from western Himalaya, India. Along with that, distribution and taxonomic remarks on species Symbrenthia niphanda Moore and Symbrenthia brabira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These species include Troides spp., H. epicles, Symbrenthia spp. and Euthalia malaccana (Fruhstorfer, 1899), and Dichorragia nesimachus (Boisduval, 1836) (Saha and Das 2012; Mehra et al 2018;Bhowmik and Chowdhury 2021;Peggie et al 2021). The result showed that butterflies could be bioindicators either in terms of the diversity of environmental characteristics (abundance and vegetation diversity) or sensitivity to environmental conditions (temperature, humidity, light intensity, wind speed, as well as the presence of pollutants) (Ghazanfar et al 2016;Comay et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These species include Troides spp., H. epicles, Symbrenthia spp. and Euthalia malaccana (Fruhstorfer, 1899), and Dichorragia nesimachus (Boisduval, 1836) (Saha and Das 2012; Mehra et al 2018;Bhowmik and Chowdhury 2021;Peggie et al 2021). The result showed that butterflies could be bioindicators either in terms of the diversity of environmental characteristics (abundance and vegetation diversity) or sensitivity to environmental conditions (temperature, humidity, light intensity, wind speed, as well as the presence of pollutants) (Ghazanfar et al 2016;Comay et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Oriental nymphalid butterfly genus Symbrenthia Hübner, 1819 (Nymphalinae), commonly called jesters, belongs to the tribe Nymphalini which has 14 recognized species (Fric et al, 2004, 2022; Kunte, 2010), mainly distributed in the Oriental region and reaching New Guinea and the eastern Palaearctic (Bozano & Floriani, 2012). Symbrenthia lilaea Hewitson, 1864, the common jester, is distributed primarily in India, China, Nepal, Bhutan, Myanmar, and Pakistan (Mehra et al, 2018). An adult female of S. lilaea was collected from Debregeasia sp.…”
Section: Methodsmentioning
confidence: 99%
“…Symbrenthia lilaea Hewitson, 1864, the common jester, is distributed primarily in India, China, Nepal, Bhutan, Myanmar, and Pakistan (Mehra et al, 2018). An adult female of S. lilaea was collected from Debregeasia sp.…”
Section: Taxon Sampling Dna Extraction and Sequencingmentioning
confidence: 99%